Interactions Between Rotylenchus reniformis and Pineapple mealybug wilt associated virus-1 in Pineapple - Sipes, B S (Plant disease, 2002)
The individual and combined effects of Pineapple mealybug wilt associated virus-1 (PMWaV-1) infection in pineapple, Ananas comosus, and Rotylenchus reniformis on pineapple growth were evaluated under greenhouse and field conditions. Under greenhouse conditions, no effect of PMWaV-1 infection on pineapple growth or nematode reproduction was observed. Under field conditions, the interaction of PMWaV-1 and nematodes was evaluated in plant and ratoon crops. In the plant crop, pineapple in plots treated with the nematicide 1,3-dichloropropane showed increased vegetative growth, whereas virus infection had no effect on vegetative growth. Nematodes reduced the average fruit weight (P = 0.01), whereas PMWaV-1 infection did not (P > 0.14). However, more fruit in the largest size classes (sizes 7 and 8) were produced in PMWaV-1-free plots than in PMWaV-1-infected plots (P = 0.03). The average fruit weight decreased in the presence of virus or nematodes. The smallest fruits were from PMWaV-1-infected plants infested with R. reniformis. More early-ripening fruit (30%) were produced by plants infected with PMWaV-1 than by PMWaV-free plants (P < 0.05). PMWaV-1 infection may be one of the reasons for asynchronous fruit ripening, which is a top limiting factor for pineapple production in Hawaii. In the ratoon crop, PMWaV-1 infection reduced fruit weight by 9% (P < 0.01), whereas nematode effects were similar across treatments (P > 0.10). More fruit in the three largest size categories were produced in PMWaV-1-free plots than in PMWaV-1-infected plots (P < 0.01). PMWaV-1 infection reduced the number of fruit produced in the ratoon crop (P < 0.02). An interaction (P < 0.03) between R. reniformis and PMWaV-1 infection status was detected in the ratoon crop. The fewest fruit were produced in plots with PMWaV-1-infected plants that were nematode infected